Hisbah and Sharia Law Enforcement in Metropolitan Kano (2011)
The reintroduction of Sharia in the twelve states of northern Nigeria between 1999 and 2000 underscores the salience of Islam in the politics and governmentalities of the region. Popular pressure led to the reintroduction of Sharia in Kano, but its trajectory signified usage for administrative convenience and legitimacy prompted by the challenges of democratic change. The reintroduction of Sharia was a convergence of state Islam and popular Islam. Hisbah was established to enforce a distinctive Islamic government. It tackles the problems of community security in a different way, dedicated to the abolition of the business and consumption of beer, the restriction of sex work, the segregation of the sexes in public spaces, and the policing of a moral order based on Sharia.